PENGGUNAAN MODALITAS CALON LEGISLATIF PEREMPUAN PADA PEMILU LEGISLATIF KOTA PEKANBARU PERIODE 2019-2024 - Raja Kurnia Febrian; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The purpose of this study is to know and understand in depth the use of the modalities of elected female legislators in the 2019 Pekanbaru City Legislative Election.This study uses the theory of Pierre Bourdieu (1986), in his book The Forms of Capital. According to Pierre ourdieu, modality is divided into four forms of capital, namely economic apital, cultural capital, social capital, and symbolic capital. The capital owned by legislative candidates must of course be optimized in order to chieve a desired or desirable goal. The methodology used in the preparation of this thesis uses a qualitative method, namely nterviews with several members of the Pekanbaru City DPRD for the 2019-2024 period who are women as legislative candidates in the 2019 egislative Elections, then collect data, organize and classify data. While the analysis is descriptive in nature which describes the form of modality in political contestation carried out by female legislators in the 2019 Pekanbaru City regional legislative elections. In this research, in the 2019 election contest for legislative members in Pekanbaru City, emale legislative candidates for Pekanbaru City have quite strong modalities both in terms of economic, symbolic, cultural and social capital. On the other hand, the use of all this capital greatly influences the community, so that the community can give their trust and upport to the female legislative candidates for Pekanbaru City for the 2019-2024 period. As for the results of this study it can be concluded that the economic capital optimized by Hj. Arwinda Gusmalina, ST and Sovia Septiana, S.Sos for their election as members of the Pekanbaru City DPRD for the 2019-2024 period. Keywords: Usage, Modality, Legislative Election 201